8x-3(-5x+2)=6

Simple and best practice solution for 8x-3(-5x+2)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3(-5x+2)=6 equation:


8x-3(-5x+2)=6

We simplify the equation to the form, which is simple to understand
8x-3(-5x+2)=6

Reorder the terms in parentheses
8x+(+15x-6)=6

Remove unnecessary parentheses
+8x+15x-6=+6

We move all terms containing x to the left and all other terms to the right.
+8x+15x=+6+6

We simplify left and right side of the equation.
+23x=+12

We divide both sides of the equation by 23 to get x.
x=0.521739130435

See similar equations:

| 2p*3p= | | (x-6)2=18 | | 9x^2-18x+7=0 | | x^2-5.38516+7=0 | | p-(-3q)= | | x-3=2x+4 | | 5-3x-7x=35 | | 8+7x+x^2=0 | | t-2=5j+s | | x^2=9(x-5) | | 7x(56-45)=8x+4 | | x^2=9(w-5) | | 0=x^2-8x+1 | | x+3y-(-2x)= | | p-(-3p)= | | -18v=3(12v+18) | | 4p+2q-(-3p)= | | 4x^2-10x+4= | | 7x^2-x-.5=0 | | 3a-(-4a)= | | 1y^2-28y-98=0 | | X+.20X=352 | | 7r+9=44 | | x^2+21x+110=0 | | 6(2n-1)=(8n+5)+4 | | x^22+21x+110=0 | | 6x^2-24x+16=-2 | | -56=8y | | 8(3n-4)=(2n+9)+5 | | 35x^2-8x-16=0 | | 35x^2+14x+7=0 | | (y-7)(y-7)+y^2=(y+7)(y+7) |

Equations solver categories